Is Earnings Quality Associated with Corporate Social Responsibility? - Kim, Yongtae; Park, Myung Seok; Wier, Benson (The Accounting Review, 2012)
ABSTRACT This study examines whether socially responsible firms behave differently from other firms in their financial reporting. Specifically, we question whether firms that exhibit corporate social responsibility (CSR) also behave in a responsible manner to constrain earnings management, thereby delivering more transparent and reliable financial information to investors as compared to firms that do not meet the same social criteria. We find that socially responsible firms are less likely (1) to manage earnings through discretionary accruals, (2) to manipulate real operating activities, and (3) to be the subject of SEC investigations, as evidenced by Accounting and Auditing Enforcement Releases against top executives. Our results are robust to (1) controlling for various incentives for CSR and earnings management, (2) considering various CSR dimensions and components, and (3) using alternative proxies for CSR and accruals quality. To the extent that we control for the potential effects of reputation and financial performance, our findings suggest that ethical concerns are likely to drive managers to produce high-quality financial reports. Data Availability: Data used in this study are available from public sources identified in the study.